Read write own : building the next era of the Internet - Dixon, Chris, 1972- (Random House, 2024)
"The Internet of today is a far cry from its early promise of a decentralized, democratic network of creativity and innovation. In the past decade, the Internet has fallen under the control of a tiny group of massive companies like Apple, Google, and Facebook. In Read Write Own, tech visionary Chris Dixon argues that the dream of an open network for fostering creativity and entrepreneurship doesn't have to die, and that in fact it can, and must, be saved with blockchain networks, which he vitally separates from the currency-based speculation that it is unfortunately lumped together with - a distinction he calls "The Computer vs The Casino". With lucid and compelling prose - and drawing from his first-hand observations, mental models, and experiences over a 25-year career in the Internet industry - Dixon shows how the Internet has undergone three distinct eras, bringing us to the critical moment we're in today. The first act was the "read era," lasting from 1990 to 2005, in which early Internet networks democratized information. In the "read-write era," 2006-2020, corporate networks democratized publishing. And we are now entering the "read-write-own era," sometimes called web3, in which blockchain networks have begun to democratize ownership, granting power and economic benefits to the participants in the network--not just to massive corporations"--